Identifying Risks and Opportunities in Outpatient Surgical Patient Safety: A Qualitative Analysis of Veterans Health Administration Staff Perceptions. Issue 3 (April 2021) - Mull, Hillary J.; Rosen, Amy K.; Charns, Martin P.; Itani, Kamal M.F.; Rivard, Peter E.
Abstract : Objectives: Little is known about patient safety risks in outpatient surgery. Inpatient surgical adverse events (AEs) risk factors include patient- (e.g., advanced age), process- (e.g., inadequate preoperative assessment), or structure-related characteristics (e.g., low surgical volume); however, these factors may differ from outpatient care where surgeries are often elective and in younger/healthier patients. We undertook an exploratory qualitative research project to identify risk factors for AEs in outpatient surgery. Methods: We developed a conceptual framework of patient, process, and structure factors associated with surgical AEs on the basis of a literature review. This framework informed our semistructured interview guide with (1) open-ended questions about a specific outpatient AE that the participant experienced and (2) outpatient surgical patient safety risk factors in general. We interviewed nationwide Veterans Health Administration surgical staff. Results were coded on the basis of categories in the conceptual framework, and additional themes were identified using content analysis. Results: Fourteen providers representing diverse surgical roles participated. Ten reported witnessing an AE, and everyone provided input on risk factors in our conceptual framework. We did not find evidence that patient race/age, surgical technique, or surgical volume affected patient safety. Emerging factors included patient compliance, postoperative patient assessments/instruction, operating room equipment needs, and safety culture. Conclusions: Surgical staff are familiar with AEs and patient safety problems in outpatient surgery. Our results show that processes of care undertaken by surgical providers, as opposed to immutable patient characteristics, may affect the occurrence of AEs. The factors we identified may facilitate more targeted research on outpatient surgical AEs. Abstract : Supplemental digital content is available in the text.